Impact of Drought on the Life Cycle of Barge Transport - Breno Tostes de Gomes Garcia; Alexandre Simas de Medeiros; Filipe Almeida Corrêa do Nascimento; Marcelino Aurélio Vieira da Silva (Salehan Institute of Higher Education, 2022)
This paper aims to analyze the impact of drought on the life cycle of barge transportation. The LCA method was used to quantify the environmental impact of barge transportation services on the Madeira River/Brazil: Transportation Operation, Barge Fleet, and Waterway Infrastructure. A model for barge convoy formation was developed as a function of river water level variation. From this, the transport operation was simulated, considering the loading of grains from the Madeira River in 2021, as well as the respective fuel consumption and CO2Eq emissions. The results indicate that barge transportation is more harmful to the environment during drought, since only a convoy of nine barges is allowed to navigate, and its energy efficiency is compromised due to the longer travel time and lower loading capacity in one trip. The intense use of this barge convoy implied an increase of 22.25% in CO2Eqemissions when compared to the full river. Doi: 10.28991/CEJ-2022-08-12-02 Full Text: PDF